Oceanographic conditions and analysis of walleye pollock Theragra chalcogramma fishery in the Navarin area in 2017–2021 - E. V. Gritsay; M. A. Stepanenko (Известия ТИНРО, 2022)
The northwestern Bering Sea, in particular the waters at Cape Navarin, is one of the main areas of the walleye pollock fishery. Environmental variability in the Bering Sea affects on recruitment, abundance, behavior, and seasonal spatial distribution of pollock, which challenge on the fishery management strategy. Understanding of environmental-driven changes in the pollock population has to improve predictions of the population dynamics and affect positively on the commercial harvest. The pollock from the eastern Bering Sea migrate to the Navarin area in summer-fall season. This study demonstrates that great annual differences in the migration activity, spatial distribution of pollock and fishery are related with oceanographic conditions, zooplankton productivity, the population reproduction, year-classes abundance and total biomass. Appearance of the relatively abundant year-classes in 2017–2020 may lead to some increase in commercial part of the pollock population in 2022–2024.